Motyw dążenia do doskonałości w Snach o potędze Leopolda Staffa - Kowalska, Olga (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The article presents the analysis of the occurrences of motifs of the pursuit of perfection in the debut poetry volume by Leopold Staff – Dreams of Power. It explains the meaning of the concept of perfection presented by the author and specifies the philosophical definition of the term. It describes the opposing elements of Staff’s early lyric towards the decadent mainstream and summons the foundations of the author’s ideological point of view based on Nietzsche an philosophy. It shows the fulfilment of his first innovative designs in youthful compositions by presenting specific themes.